Do cientista ao ativista: os problemas da ciência do texto e uma solução revolucionaria na obra de Terry Eagleton - Marinho, Andrew Yan Solano (2014)
The literary critic Terry Eagleton obtained notoriety in academic circles when he was recognized intellectually for his bestselling book Literary Theory: An Introduction. In this book, the English author boldly proposes the end of literature and literary criticism. However, Eagleton proposed years before, in his book Criticism and Ideology (1976), a scientific system of analysis of literary texts, which seemed less radical, both in theory and in method, than in his later theoretical proposal. Based on this, the objective of this dissertation is to present the English literary critic´s initial method, explaining the reasons that led him to abandon his initial project - of develop a method of analysis of the literary text on a Marxist scientific perspective - and to propose, in the following years, in his most famous book and others, a revolutionary vision that would go beyond textual analysis and make literary texts have a practical intervention in society. Finally, we explain what would be his idea of revolutionary criticism